Prevalence and risk factors associated with Leishmania spp. and Trypanosoma cruzi infections in dogs presented at veterinary clinics in Joao Pessoa, Paraiba state, northeastern Brazil - Lima Brasil, Arthur Willian de; Ribeiro Machado, Dalia Monique [UNESP]; Ramos Xavier da Silva, Mariana Aimee [UNESP]; Barrosa, Noelle de Castro [UNESP]; Sousa Silva, Raizza Barros; Melo, Marcia Almeida de; Langoni, Helio [UNESP]; Americo Batista Santos, Carolina de Sousa; Azevedo, Sergio Santos de (Univ Estadual Londrina, 2018)
This study aimed to determine the prevalence and risk factors associated with Leishmania spp. and Trl.panosoma cruzi infections in dogs presented at veterinary clinics in the city of JoAo Pessoa, Paraiba state, northeastern Brazil. A total of 384 dogs from 34 veterinary clinics were sampled between April 2015 and May 2016. For serological diagnosis of canine visceral leishmaniasis and Chagas disease, the indirect fluorescent antibody test was used. Reactive sera were submitted to a confirmatory test using the S7 ELISA. The seroprevalence of Leishmania spp. was 2.8% (11/384), and that of T. cruzi was 1.5% (6/384). Two animals were positive for both parasites. The variable access to the street was identified as a risk factor for Leishmania spp. infection (OR = 4.81; 95% CI = 1.23-18.75). We concluded that a significant proportion of dogs presented at veterinary clinics in Joao Pessoa are seropositive for Leishmania spp. or T cruzi infections, and we suggest that greater care be taken with dogs that have access to the street.
Keywords: Leishmaniosis; Chagas disease; Urban environment; Domiciled dogs; Northeastern Brazil